15N-labelled fertiliser recovery by maize (Zea mays L.) and leaching of nutrients as influenced by oil palm empty fruit bunch biochar in a mini-lysimeter under controlled tropical environment. Issue 12 (15th October 2017) - Lee, Sherwin Chan Kit; Rosenani, Abu Bakar; Ishak, Che Fauziah; Idris, Azni; Abdul Rahim, Khairuddin; Meyer-Aurich, Andreas
ABSTRACT: Converting oil palm empty fruit bunches into biochar is an alternative waste management method and has strong potential to improve N fertiliser use efficiency in agriculture. The aim of this study was to determine the effectiveness of oil palm empty fruit bunch biochar (EFBB) in improving recovery of 15 N-labelled nitrogen fertiliser by maize ( Zea mays L.) and leaching of mineral N and K. An experiment was conducted in a mini-lysimeter system with randomised complete block design layout and six replications under controlled environment in a rain shelter. Each mini-lysimeter was filled with 20 kg of sandy loam soil before adding EFBB (0, 5, 10 and 20 Mg ha −1 ). The N source used was ( 15 NH4 )2 SO4 at 80 kg N ha −1 (2 at% 15 N excess). Maize was irrigated to induce leaching every 4 days. Maize plant and soils were sampled 58 days after sowing (tasselling stage). Application of EFBB significantly reduced cumulative leachate volume and mineral N leaching. Soils applied with EFBB significantly improved 15 N fertiliser recovery in maize and dry matter weight. This study shows that EFBB has the potential to be applied on highly weathered acidic soil as an amendment to improve fertiliser efficiency and crop growth.